2007
DOI: 10.1104/pp.106.094953
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Roles of ADP-Ribosylation Factor 1 in Plant Cells Include Spatially Regulated Recruitment of Coatomer and Elements of the Golgi Matrix

Abstract: Recent evidence indicates that ADP-ribosylation factor 1 (ARF1) carries out multiple roles in plant cells that may be independent from the established effector complex COPI. To investigate potential COPI-independent functions, we have followed the dynamics of ARF1 and a novel putative effector, the plant golgin GRIP-related ARF-binding domain-containing Arabidopsis (Arabidopsis thaliana) protein 1 (GDAP1) in living plant cells. We present data that ascribe a new role to ARF1 in plant cell membrane traffic by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(88 citation statements)
references
References 42 publications
6
82
0
Order By: Relevance
“…ARF1 is known to recruit coatomer to Golgi membranes. However, it has also been shown recently that ARF1 is capable of recruiting an additional effector, the golgin GDAP1, to the Golgi and post-Golgi organelles in plant cells (Matheson et al, 2007). FRAP analyses on fluorescent protein fusions of ARF1, coatomer, and GDAP1 have shown that the cycles of binding and release of ARF1 to and from the Golgi apparatus are similar to those of GDAP1 but faster than coatomer (Fig.…”
Section: Fluorescence Recovery After Photobleachingmentioning
confidence: 99%
See 3 more Smart Citations
“…ARF1 is known to recruit coatomer to Golgi membranes. However, it has also been shown recently that ARF1 is capable of recruiting an additional effector, the golgin GDAP1, to the Golgi and post-Golgi organelles in plant cells (Matheson et al, 2007). FRAP analyses on fluorescent protein fusions of ARF1, coatomer, and GDAP1 have shown that the cycles of binding and release of ARF1 to and from the Golgi apparatus are similar to those of GDAP1 but faster than coatomer (Fig.…”
Section: Fluorescence Recovery After Photobleachingmentioning
confidence: 99%
“…In studies of plant endomembranes, FRAP has been used relatively recently in establishing the nature of the factors that influence protein traffic dynamics from the ER to the Golgi apparatus (Brandizzi et al, 2002b) and the dynamics of the proteins that regulate ER-to-Golgi protein transport (daSilva et al, 2004;Yang et al, 2005). With a similar approach, it has been recently shown that the small GTPase ARF1 binds to and is released from Golgi membranes at a rapid turnover rate (Stefano et al, 2006;Matheson et al, 2007). ARF1 is known to recruit coatomer to Golgi membranes.…”
Section: Fluorescence Recovery After Photobleachingmentioning
confidence: 99%
See 2 more Smart Citations
“…RGA was then calculated as a percentage of the total fluorescence of both areas: RGS(PS/C)ϫ100. Measurements were performed on images acquired with the same microscope intensity settings (Matheson et al, 2007).…”
Section: Microscopymentioning
confidence: 99%